Pelayanan Prima dalam Rangka Peningkatan Kapasitas SDM Bagi Pengelola Homestay Untuk Mendukung Pengembangan Industry Pariwisata di Provinsi Banten - Hidayat, Candra (Jurnal Pemberdayaan Pariwisata, 2020)
Banten Province is located in the West Cape of Java, positioning Banten as the gateway to Java and Sumatra and directly bordering the DKI Jakarta area as the National Capital. This geostrategic position certainly causes Banten as the main link of the Sumatra-Java trade route and even as part of Asian and International trade circulation and as a potential agglomeration of economic and settlement locations. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously can minimize weaknesses  and threats. The purpose of training is carried out by seminar to increase the knowledge and understanding of Homestay managers in order to provide excellent service and customer satisfaction, with the number of participants as many as 30 people from the management of the Homestay in the province of Banten. Based on what has been done, the results are: 1. Homestay managers get support from the Banten provincial government and the Banten Provincial Tourism Office. 2. Weaknesses and Threats of SWOT Analysis for Homestay managers in Banten province are not major obstacles, because these things can be overcome with ongoing training. 3. The homestay managers get a good standard operating procedure from the training. So that, the Homestay managers can provide excellent service and the tourists who stay overnight feel satisfied and then come back and recommend it.